Video Art and Collective Memory in Turkey (Imaginations: Journal of Cross-Cultural Image Studies, 2025)
Turkey's thriving art scene reflects the growing interest in the international contemporary art market in countries outside the Western world. Istanbul has become a major hub of cultural exchange between the Eastern Mediterranean region, the Caucasus, and the Middle East. Video art is a popular art form in Turkey, and its popularity has been growing in recent years. The aim of this article is to present and study contemporary video practices since the 2000s in Turkey through the representation of time and collective memory. The article presents the four video artists who have structured the video art scene in Turkey: Ali Kazma, Halil Altındere, Erkan Özgen and Seza Paker. The selected videos present autobiographical memories or references to collective memory to explore how time is represented in video art.